Art Theory: A Very Short Introduction - Freeland, Cynthia (Oxford Oxford University Press, 2001)
Admirable for its compactness, reader-friendliness, this 'very short introduction' is nevertheless notable for its wide-ranging discussion of matters germane to the field of contemporary art. Should be a treat for the art-lovers amongst the academics. (U.S.I. Journal )
Keywords: Esthetics; Fine art